What Greek mothers know about evaluation and treatment of fever in children: An interview study - Matziou, Vasiliki N.; Brokalaki, Hero; Kyritsi, Helen; Perdikaris, Pantelis; Gymnopoulou, Elpida; Merkouris, Anastasios (My University, 2008)
Background Fever is one of the most common symptoms in childhood. Mothers’ insufficient knowledge about its evaluation and treatment frequently leads to excessive fear and anxiety. Objectives To explore mothers’ knowledge concerning management of fever in their children, at home. Design Descriptive, correlational. Settings An emergency department of a pediatric hospital. Participants A total of 327 mothers with febrile children randomly selected in the waiting room. Methods Data collection was based on interviews by using a questionnaire which was specifically developed for this study. Results Almost one out of three mothers (32.4%) evaluated fever as a temperature between 37–38 °C and the 38.1% of them considered that side effects could be a result of these temperatures. The majority of the mothers (73.7%) administered antipyretics at body temperatures of 37–38.5 °C, usually without a medical instruction (49.2%). Younger mothers with lower education levels and those who admitted to hospital for the first time with children less than 12 months of age showed the poorest level of Knowledge about fever evaluation and treatment. Conclusions Educational interventions by health care professionals aiming at educating young mothers with a low educational level and those with a child younger than 12 months old who seek medical attention at hospital, for the first time, are needed to dispel misconceptions about fever and to promote the appropriate management of the febrile child.
Keywords: Children; Fever knowledge; Fever management; Home; Mothers